Kajian Literatur Sistematis: Luxury Brand - Khaeril, Khaeril (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2021)
Luxury brand as trend is became Interesting Issue to discus by Scholars and Practicion and knowing the Important for managerial to make decition. Literature review was Implemented as methode is a literature review using publish or perish software for data mining and Vos Viewer for data analysis and visualization. The research findings show that there are 12 research clusters on luxury brands. The articles that became the main reference in research for the Lux brand in less than 2005-2020 were Michaut-Anne, Jean-Noel Kapferer, Valette-florence, Pierre. Based on the research findings, we conclude that the luxury brand research gap is still wide open, especially in Indonesia.